Public employment programs - Fechter, Alan. (Washington : American Enterprise Institute for Public Policy Research, 1975)
This book examines various programs established to outlived the human capacity deficiency in the American society. The evaluation was based on employment enrollment and human gap to achieve development.
Includes bibliographical references.
asm; 12/02/19
Loans
Keywords: Manpower policy; Local officials and employees; State governments